(3MjGI GdbdhHs - (3GdSfhdj, fHj Hf WhQNGf Hf WhQT ` cGf MjG (B930 (3g`s ((3CMeO Hf GdMGL YKeGf LGfj RGOgs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj gOGfG HGdbQBf GdeLjO GeG HYO aEf CVYa YHGO Gddg fHj Hf WhQNGf jbhd hQCjJ Cf efUa cd cJGH ef GdJaGSjQ hGdCMGOjK hGdeTQhYGJ djShG HejJjf aWGdYJ ef GdeDdaGJ ef af GdMOjK GdHNGQj heSde ahLOJ HYV GdCMGOjK eY CSGfjOg (B( (3cPG (B) (3hSejJg HMjGI GdbdhHs
(3BNQgG (B:s
(3aEf cQeg YGe hQMeJg hGSYI hfMf Ndb Gddg YR hLd dG hSjdI dfG Edjg EdG HaVdg hcQegs
(3efShNI Yf fSNI GdeDda GdeDQNI SfI (B930 (3g`s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdJedcGJ h GdhbajGJ (B:s
Keywords: (3GdMOjK hGdeUWdMs